Penyuluhan Fisioterapi terhadap Ibu Hamil dengan Memberikan Senam Hamil untuk Menjaga Kebugaran Ibu Hamil di Puskesmas Cicalengka Bandung - Abdul Qudus; Irda Sari; Ika Rahman; Ade Irma Suryani; Ara Ariska (LPPM Politeknik Piksi Ganesha, 2023)
Pregnancy is an important period that requires special attention to the physical and mental health of the mother. One of the efforts to maintain the fitness and physical readiness of pregnant women in facing childbirth is through pregnancy exercises facilitated by physiotherapists. This community service activity aims to increase the knowledge and skills of pregnant women in performing pregnancy exercises independently and safely. The methods used in this activity include health education, pregnancy exercise demonstrations, and evaluation of participants' knowledge and satisfaction levels. The activity was held at the Cicalengka Community Health Center in Bandung with 30 pregnant women participating. The results of the activity showed an increase in participants' understanding of the importance of physical activity during pregnancy, as well as an increase in participation in performing prenatal exercises regularly. This activity demonstrates that education and physiotherapy assistance play an important role in maintaining the fitness of pregnant women and encouraging healthy pregnancies and safe childbirth.